Analisis Faktor Lingkungan Terhadap Prevalensi Stunting Pada Balita Di Desa Mana Resmi Kabupaten Musi Rawas - Hartika, Citra; Suharyanto; Santoso, Urip; Yurike; Brata, Bieng (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
This study aims to analyze the influence of latrine ownership, availability of clean water, and the influence of hand washing habits on the incidence of stunting. This research was conducted in the ManaOfficial Village, Muara Beliti District, Musi Rawas Regency, South Sumatra. The data collection technique uses total sampling, namely the entire population is used as a sample. The sample in this study were all toddlers in the Mana Official Village totaling 194 toddlers. The data instrument was adapted from the IKL (environmental health inspection) form for the availability of clean water, toilet ownership, and the habit of washing hands with soap from the District Health Office. Musi Rawas in 2023. Data analysis used the Chi-square test. The results showed that there was a significant relationship between latrines ownership, availability of clean water, and the habit of washing hands with soap (CPTS) on the incidence of stunting in the ManaOfficial Village area, Musi Rawas Regency, in 2023.